Constitutive androstane receptor, liver pathophysiology and chemical contaminants: current evidence and perspectives - De Battistis, Francesca; Djordjevic, Aleksandra Buha; Saso, Luciano; Mantovani, Alberto (Frontiers in Endocrinology, 2025)
IntroductionThe Constitutive Androstane Receptor (CAR) (NR1I3), a pivotal member of the xenosensor family, plays a key role in the hepatic detoxification of xenobiotic and endobiotic chemicals through the induction of the expression of drug-metabolizing enzymes and transporters. CAR’s involvement extends beyond detoxification, influencing gluconeogenesis, lipogenesis, bile acid regulation, and cellular processes such as proliferation, tissue regeneration, and carcinogenesis. This review explores CAR regulation by various factors, highlighting its role in mediating metabolic changes induced by environmental contaminants.MethodsA literature search was conducted to identify all articles on the PubMed website in which the CAR-contaminant and CAR-hepatic steatosis relationship is analyzed in both in vitro and in vivo models.ResultsNumerous contaminants, such as perfluorooctanoic acid (PFOA), Zearalenone mycotoxin, PCB, triazole fungicide propiconazole can activate hepatic nuclear receptors contributing to the development of steatosis through increased de novo lipogenesis, decreased fatty acid oxidation, increased hepatic lipid uptake, and decreased gluconeogenesis. Indirect CAR activation pathways, particularly involving PFOA, are discussed in the context of PPARα-independent mechanisms leading to hepatotoxicity, including hepatocellular hypertrophy and necrosis, and their implications in nonalcoholic steatohepatitis (NASH) and nonalcoholic fatty liver disease (NAFLD). The prevalence of NAFLD, a significant component of metabolic syndrome, underscores the importance of understanding CAR’s role in its pathogenesis.ConclusionsExperimental and epidemiological data suggest that endocrine disruptors, especially pesticides, play a significant role in NAFLD’s development and progression via CAR-regulated pathways. This review advocates for the inclusion of modern toxicological risk assessment tools, such as New Approach Methodologies (NAMs), Adverse Outcome Pathways (AOPs), and Integrated Approaches to Testing and Assessment (IATA), to elucidate CAR-mediated effects and enhance regulatory frameworks.